The Relation between Flow Map Analysis and Residential Density Conditions in Sleman Regency, Special Region of Yogyakarta - Trimarstuti, Jeki; Tulus Wahyuhana, Ratika; Hyun Kim, Ji (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
The government of Sleman Regency has been actively implementing the Smart Living concept within the Smart Regency framework where its key achievements include developing type C terminal facilities, creating a transport licensing management information system, and collecting data on public transport modes and routes. However, complete access and integration of public transportation with all government facilities, such as hospitals, schools, and offices, remain unrealized. Thus, this research examines the relationship between flow map analysis and residential density in Sleman Regency, based on data from local residents, to address these integration challenges. The analysis was conducted using quantitative methods, especially ArcGIS. Research data were collected through interviews, questionnaire distribution, and observation throughout the regency. The results showed that the current form of movement patterns originates from residential areas with a high density (in terms of population), which has been visualized using flow map analysis and tends to determine no relationship between the daily movement patterns and the residential density conditions. It is because the current form of movement patterns in high-density areas, which are based on the respondent's preferences of transportation mode, has yet to be served well by existing urban bus services. Therefore, the tendency to choose the location of a residential area is independent of the absence or availability of public transportation itself. In the future, all of the unserviced areas should be part of the government's concern so that the idea of connected communities can be implemented and the idealization of the Smart Living concept in Sleman Regency.